The ecology of rodent pollination in Liparia parva (Fabaceae) - Letten, Andrew (Department of Biological Sciences, 2017)
The evolution of non-flying mammal pollination has given rise to a broad suite of adaptive plant traits including dull coloured and geoflorous flowers, copious sucrose rich nectar, nocturnal anthesis and nectar production and a musky odour. The Fynbos endemic, Liparia parva (Fabaceae) has been recognised to exhibit several of these traits. Based on this observation, field studies were carried out on the Cape Peninsula, South Africa, to investigate the prediction that L. parva is rodent pollinated. Several lines of evidence indicate that flowers of L. parva are visited by rodents. These include; the presence of Liparia pollen in the faeces of live trapped rodents; observations of captive rodents selectively foraging at flowers of L. parva; floral debris underneath L. parva plants; and video footage captured of a rodent visiting L. parva flowers in the field. However, a strong plant-pollinator relationship was apparent only in the Cape spiny mouse, Acomys subspinosis. Captive Acomys foraged non-destructively at flowers of L. parva, becoming visibly dusted with pollen. The exclusion of rodents from flowers resulted in a significant reduction in seedpod set, indicating rodents do contribute to pollination success in L. parva. Additional evidence that L. parva is adapted to pollination by rodents includes nocturnal floral anthesis and large amounts of total nectar in inflorescences. The findings of this study provide substantial evidence for rodent pollination in L. parva and thus represent the first report of rodent pollination in a legume.